2023
DOI: 10.1186/s11689-022-09469-3
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical morphological alteration in Angelman syndrome

Abstract: Background Angelman syndrome (AS) is a neurodevelopmental disorder with serious seizures. We aim to explore the brain morphometry of patients with AS and figure out whether the seizure is associated with brain development. Methods Seventy-three patients and 26 healthy controls (HC) underwent high-resolution structural brain MRI. Group differences between the HC group and the AS group and also between AS patients with seizure (AS-Se) and age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In healthy individuals, during development, cortical thinning is directly associated with increased cortical connectivity (Ball et al, 2019; Storsve et al, 2016). Most studies on cortical thickness in genetic syndromes associated with intellectual disability have reported a normal hemispheric or global cortical thickness compared to the healthy population, except for significant variations in brain parcel areas, either because they are increased or decreased (Du et al, 2023; Fahim et al, 2012; Giedd et al, 2007; Kippenhan et al, 2005; Levman et al, 2019). On the other hand, cortical thickness in overgrowth syndromes has been scarcely studied; most studies have shown a normal or even decreased cortical thickness (Zamary & Mamlouk, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, during development, cortical thinning is directly associated with increased cortical connectivity (Ball et al, 2019; Storsve et al, 2016). Most studies on cortical thickness in genetic syndromes associated with intellectual disability have reported a normal hemispheric or global cortical thickness compared to the healthy population, except for significant variations in brain parcel areas, either because they are increased or decreased (Du et al, 2023; Fahim et al, 2012; Giedd et al, 2007; Kippenhan et al, 2005; Levman et al, 2019). On the other hand, cortical thickness in overgrowth syndromes has been scarcely studied; most studies have shown a normal or even decreased cortical thickness (Zamary & Mamlouk, 2022).…”
Section: Discussionmentioning
confidence: 99%